O-31 Synthesis of evidence from the PROTECT UK national core study: exploring occupational risks of SARS-CoV-2 infection and COVID-19 mortality. (14th March 2023) - Tongeren, Martie van; Rhodes, Sarah; Beale, Sarah; Pearce, Neil; Cherrie, Mark; Holland, Fiona; Hayward, Andrew; Gittins, MAtthew; Mueller, Will
Abstract : Introduction: The PROTECT National Core Study was funded by the UK Health and Safety Executive (HSE) to investigate how SARS-CoV-2 is transmitted from person to person, and how this varies in different settings. One area of research aimed to compare relative differences between occupational groups and sectors in SARS-CoV-2 infection and COVID-19 mortality over time and explore the likely reasons. Methods: We brought together evidence from nine published epidemiological studies supported by PROTECT relating to four data sets, plus new analyses relating to the Omicron period. We organised these studies into the following categories: those that specifically compared risks of infection mortality; and those that looked at risk factors for SARS-CoV-2 infection and/or COVID-19 mortality. We extracted descriptive study level data and results. We investigated risk across four pandemic waves using forest plots for key occupational groups by time. A workshop was organised in Oct 2022 with authors from each study to discuss and document key strengths and expected biases. Results: Healthcare and social care sectors saw elevated risks of SARS-CoV-2 infection and COVID-19 mortality early in the pandemic but thereafter these declined and varied by specific occupational subgroup. The education sector saw sustained elevated risks of infection after the initial lockdown period with little evidence of elevated mortality. Results were largely consistent across different studies with differing expected biases, although unmeasured confounding cannot be ruled out. Conclusion: Differences between occupations and sectors in the UK in terms of COVID-19 risks that were observed in the early stages of the pandemic largely dissipated over time. Studies investigating risk factors suggest that reasons could include vaccination roll out, introduction of risk mitigation within high risk sectors, changes in patterns of home-working and lifting of restriction on social mixing (thereby reducing the relative effect of work).